Costs Analysis Regarding to Quality of Product - Kaziliūnas, Adolfas (Ekonomika, 1998)
A formal assessment of quality costs provides an understanding of the size of the problems and the areas demanding attention. Many organizations summarize these costs into four broad categories: internal failure costs, external failure costs, appraisal costs and prevention costs. Additional useful comparisons can be derived from the interrelationships among the subtotals of the quality costs in the major categories. Improving the quality of conformance results in a reduction of total costs over most of the horizontal spectrum. Organizations which have not yet engaged extensively in the quality improvement are likely to find their processes mainly in the improvement zone. For such organizations the main opportunities for cost reduction are through projects for improving quality conformance.